CEO power and board structure of banks: a developing country's perspective - David Adeabah (ZBW – Leibniz Information Centre for Economics, 2018)
This study examines the implications of CEO power on the board structure of banks in the Ghanaian banking industry. Using a unique hand-collected dataset in respect of 21 commercial banks in Ghana for the 2009 – 2017 periods, the results show that CEO power underscores the absence or lack of gender composition of bank boards and constrains independent directors, while incentivizing larger board size in banks. Meanwhile, ownership structure and listing status critically underpin the CEO power effect on bank board structure, such that the actual sign of the marginal effect of CEO power on bank board structure varies with ownership structure and listing status. Overall, the study contributes to the understanding of the global antecedent of bank corporate governance (i.e. board structure) by providing an understanding of the implications of social connection hypothesis on bank board structure in a developing country's context.
Keywords: G21; G30; G32; 330; CEO Power; Board Structure; Gender Diversity; Board Size; Board Independence; Social Connection